Young COVID-19 Patients Show a Higher Degree of Microglial Activation When Compared to Controls - Matschke, Jakob; Lahann, Henri; Krasemann, Susanne; Altmeppen, Hermann; Pfefferle, Susanne; Galliciotti, Giovanna; Fitzek, Antonia; Sperhake, Jan-Peter; Ondruschka, Benjamin; Busch, Miriam; Rotermund, Natalie; Schulz, Kristina; et al. (Frontiers in Neurology, 2022)
The severe acute respiratory syndrome-corona virus type 2 (SARS-CoV-2) is the cause of human coronavirus disease 2019 (COVID-19). Since its identification in late 2019 SARS-CoV-2 has spread rapidly around the world creating a global pandemic. Although considered mainly a respiratory disease, COVID-19 also encompasses a variety of neuropsychiatric symptoms. How infection with SARS-CoV-2 leads to brain damage has remained largely elusive so far. In particular, it has remained unclear, whether signs of immune cell and / or innate immune and reactive astrogliosis are due to direct effects of the virus or may be an expression of a non-specific reaction of the brain to a severe life-threatening disease with a considerable proportion of patients requiring intensive care and invasive ventilation activation. Therefore, we designed a case-control-study of ten patients who died of COVID-19 and ten age-matched non-COVID-19-controls to quantitatively assess microglial and astroglial response. To minimize possible effects of severe systemic inflammation and / or invasive therapeutic measures we included only patients without any clinical or pathomorphological indication of sepsis and who had not been subjected to invasive intensive care treatment. Our results show a significantly higher degree of microglia activation in younger COVID-19 patients, while the difference was less and not significant for older COVID-19 patients. The difference in the degree of reactive gliosis increased with age but was not influenced by COVID-19. These preliminary data warrants further investigation of larger patient cohorts using additional immunohistochemical markers for different microglial phenotypes.